2022
DOI: 10.1200/jco.21.02257
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Neutralizing Antibody Response After SARS CoV-2 Vaccination in Patients With Myeloma

Abstract: PURPOSE Vaccine-induced neutralizing antibodies (nAbs) play a critical role in protection from SARS CoV-2. Patients with B-cell malignancies including myeloma are at increased risk of COVID-19–related mortality and exhibit variable serologic response to the vaccine. The capacity of vaccine-induced antibodies in these patients to neutralize SARS CoV-2 or its variants is not known. METHODS Sera from 238 patients with multiple myeloma (MM) undergoing SARS CoV-2 vaccination were analyzed. Antibodies against the SA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
38
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(48 citation statements)
references
References 22 publications
6
38
0
Order By: Relevance
“…Using commercially available anti‐spike antibody testing, we observed that ~85% of our patients with PCD mounted a positive serological response within 6 months of completing the initial vaccination series, comparable to other previous studies. 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 In studies assessing neutralising antibodies, the serological response has been lower, ranging from 41% to 74%. 12 , 19 , 20 , 21 , 22 Although the presence and titre of neutralising antibodies may more directly reflect viral protection, these assays are not widely available in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Using commercially available anti‐spike antibody testing, we observed that ~85% of our patients with PCD mounted a positive serological response within 6 months of completing the initial vaccination series, comparable to other previous studies. 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 In studies assessing neutralising antibodies, the serological response has been lower, ranging from 41% to 74%. 12 , 19 , 20 , 21 , 22 Although the presence and titre of neutralising antibodies may more directly reflect viral protection, these assays are not widely available in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“… 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 In studies assessing neutralising antibodies, the serological response has been lower, ranging from 41% to 74%. 12 , 19 , 20 , 21 , 22 Although the presence and titre of neutralising antibodies may more directly reflect viral protection, these assays are not widely available in clinical practice. In most studies, good correlation has been observed between spike receptor‐binding domain (RBD) IgG antibody titres and inhibition capacity of neutralising antibodies, including in studies of MM 12 , 23 , 24 and for different anti‐spike RBD IgG assays utilised in this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For the initial analysis of BoAb assay, we used samples from Nooka et al, 33 who studied the neutralization determinants in myeloma patients. With this cohort, we observed that results in the BoAb assay strongly correlated with both live virus neutralization (Wuhan R 2 = 0.82 and p=<0.001; Delta R 2 = 0.80 and p=<0.001) and pseudovirus neutralization results (Wuhan R 2 = 0.72 and p=<0.001; Delta R 2 = 0.66 and p=<0.001).…”
Section: Discussionmentioning
confidence: 99%
“…Neutralization activities against SARS-CoV-2 WT (Wuh-1) and Delta (B.1.617.2) strains were measured in a single-round-of-infection assay with pseudo viruses, as previously described 33 . Briefly, to produce SARS-CoV-2 WT and Delta pseudoviruses, an expression plasmid bearing codon optimized SARS-CoV-2 full-length S plasmid (parental sequence Wuhan-1, Genbank #: MN908947.3) was co-transfected into HEK293T cells (ATCC#CRL-11268) with plasmids encoding non-surface proteins for lentivirus production and a lentiviral backbone plasmid expressing a Luciferase-IRES-ZsGreen reporter, HIV-1 Tat and Rev packing plasmids (BEI Resources) and pseudoviruses harvested after 48 hours of post transfection and performed titration.…”
Section: Pseudovirus Neutralization Assay (Pna)mentioning
confidence: 99%